Recreational Game Socialization Using PowerPoint as a Practical Media - Syafrinal; Taufiq Iqbal; Imilda; Fauzan Putraga Albahri; Alfina; Rizaldi Akbar (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity is a form of training for teachers and lecturers in Banda Aceh City, where the use of Microsoft Powerpoint can be adapted to make a simple game. We chose games Hidden Picture Games, Matching Game, Telepathy Game, Top Five quiz, Mystery Box, and Lucky Box. The implementation method consists of three stages, namely introduction, practice, and demonstration. The results of this activity have become a concept and collaborative learning model through recreational game media that can be used at universities in Indonesia in making service activities in utilizing Microsoft PowerPoint practical media to create innovations and develop an educational game as well as improve the ability of teachers and lecturers to utilize instructional Media.